The complete mitogenome of Argentina brasiliensis Kobyliansky, 2004 and a phylogenetic analyses of the order Argentiniformes - Claudio Oliveira; Heloísa De Cia Caixeta; Marcelo Roberto Souto de Melo (Genetics and Molecular Biology)
Abstract The deep sea environment is the largest environment and host some of the most extreme ecosystems on Earth, therefore, possessing a large and unique fish diversity that encompasses about 15% of all known species. Our knowledge about these fishes is still very limited in many biological fields basically due to the complexity to obtain specimens for research. In the present study, we describe the complete mitochondrial genome of Argentina brasiliensis, aiming a species characterization and the study of the phylogenetic relationships in the order Argentiniformes. The mitogenome is composed by 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region (D-loop), as found in other vertebrates. The phylogenetic results show that the order Argentiniformes is composed by two family groups the first formed by Argentinidae and Opisthoproctidae and the second formed by Bathylagidae and Microstomatidae. Additionally, we found that the genus Argentina is not monophyletic, and we suggest additional studies in the family Argentinidae to better investigate this question.